II Argentine Conference on Statistical Education and I Latin American Conference on Research in Statistical Education (Yupana, 2021)
The year 2020 was the year that the COVID-19 pandemic broke out, which meant that all educational, research and outreach activities have been developed virtually. This situation, which caused many complexities in various areas of life, created a favorable environment for the Latin American community interested in Statistical Education, to be able to find themselves at a distance to be able to exchange classroom experiences, teachings, learning and research results focused on the Statistical Education. The means for this meeting were the Argentine Conference on Statistical Education and the Latin American Conference on Research in Statistical Education. In this work we present a brief description of the activities carried out and mainly, we comment on the main conclusions that were obtained, from which different work projects have been generated among this learning community that are presented as the closing of this article.
Keywords: Statistics Education; statistical thinking; critical citizenship; teacher education; Literacy Statistics